2015
DOI: 10.1016/j.jad.2014.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress among pregnant migraineurs in a pacific-northwest cohort

Abstract: Background The co-occurrence of migraine and unipolar psychiatric disorders has been well documented in non-pregnant populations, however little is known in pregnant populations. Methods A cohort of 1,321 women was interviewed during the first trimester of pregnancy. At the time of interview lifetime migraine status was ascertained using International Classification of Headache Disorders diagnostic criteria (ICHD-II). Information regarding unipolar depression, anxiety and stress during pregnancy was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
(92 reference statements)
3
15
0
Order By: Relevance
“…This study showed that headache was a significant factor of antenatal depressive symptoms, which is consistent with a previous study [ 25 ]. One possibility for this observation is that Chinese people tend to somatize their depressive symptoms as a physical symptom, such as headaches [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study showed that headache was a significant factor of antenatal depressive symptoms, which is consistent with a previous study [ 25 ]. One possibility for this observation is that Chinese people tend to somatize their depressive symptoms as a physical symptom, such as headaches [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Experiencing antenatal morbidities may have a significant impact on depressive symptoms [ 20 , 21 ], especially to common antenatal morbidities, such as gestational diabetes (GDM), preeclampsia, headache, nausea, and vomiting [ 22 ]. However, previous studies showed that GDM [ 21 , 23 ], preeclampsia [ 22 , 24 ], headache [ 25 , 26 ], nausea, and vomiting [ 20 , 22 ] are not consistently associated with perinatal depressive symptoms. Moreover, the association between postnatal conditions and postnatal depressive symptoms has been explored, but the results for mode of delivery [ 27 , 28 ], gestation of infant [ 22 , 29 ], and role of newborn gender [ 28 , 30 ] are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In all the studies the results demonstrated a strong relationship in terms of Odds Ratios ( 38 ) between anxiety and migraine compared to non-migraineurs. Both the Brazilian studies ( 29 , 39 ) showed exceptionally high ORs (OR = 13 and 25 in order), with the other six studies showing ORs ranging from 1.77 to 4.5 ( 40 , 41 ).…”
Section: Resultsmentioning
confidence: 90%
“…20 This divergence in reported prevalence rates between seeking help for headache or migraine during pregnancy as opposed to non-pregnancy headache or migraine may be due to headache or migraine being related to serious illness during pregnancy including hypertension, 3 preeclampsia, 4 heart disease, 21 and depression. 22 Women may be more inclined to seek the advice of a healthcare professional if these symptoms occur during pregnancy if they perceive them to be potentially signs of more serious illness that could negatively influence the course of their pregnancy, delivery and the health of their unborn baby. In addition to the fear of complications, this vulnerable group of pregnant women with headache or migraine may also need more information from the practitioners regarding the usability and safety of routinely used treatments in pregnancy.…”
Section: Discussionmentioning
confidence: 99%